ANALISIS PERBEDAAN TINGKAT KEPUASAN PASIEN TERHADAP MUTU PELAYANAN RAWAT JALAN PUSKESMAS BERSTATUS AKREDITASI UTAMA DAN PARIPURNA DI KOTA SEMARANG - Nimas Ariyani Damayanti; Sutopo Patria Jati; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2018)
Regulation of the Ministry of Health Number 46 Year 2015 states that Health Center must be accredited regularly at least every three years. Through the accreditation, Health Center’s management is expected to apply the procedural standar well to make patients satisfied with the service provides. According to outpatient service data of Health Center in Semarang, Plenary accredited Health Center has downward trend and main accredited Health Center have upward and fluctuative trend. The purpose of this research’s to analize the difference of patient's satisfaction level at Health Care accredited as main and plenary accreditation in Semarang based on service quality dimension aspect. This research use descriptive analytic method with cross sectional design. The sample of this research is 192 respondents. Data analysis included univariate analysis with frequency distribution table and crosstab and bivariate analysis using Mann-Whitney test. The results of crosstab indicate highly educated respondents and respondents who don’t use JKN tend to be less satisfied with the services provided. The univariate result shows the satisfaction level on the quality of outpatient services in terms of the five dimensions of service quality in the Plenary accredited Health Care tend to be better than respondents from the main accredited health center. Bivariate analysis shows there’re significant differences in tangible (p <0.001), reliability (p <0.001), responsiveness (p <0.001), emphaty (p <0.001), whereas there’s no difference in assurance (p = 0.346). It’s suggested Health Center to improve the waiting room, maximize preventive promotive effort by health promotion staffs, evaluate routine waiting time, and having evaluation and monitoring to patient satisfaction about quality of service.